Training and Research: A Discussion Concerning the Jean- Jacques Rousseau Institute, of Geneva, Switzerland (1912-1947) - Carlos Jilmar Díaz Soler (Universidad Pedagógica Nacional, 2016)
The article, a research product, presents the array of the political reform that, in the late 1920s, took over the institutional and formal training teachers in Colombia. The authors discuss this training proposal as a result of requests made by some Latin American governments, and problematize the political and pedagogical thinking fostered since then in teacher training processes. Particularly, the promotion and naturalization of the link between training and research is posited as one of its results.